The Seventh Five Year Plan 1985-90 Volume 1-2 Perspective, Objectives, Strategy, Macro-Dimensions and Resources - Planning Commission (Planning Commission, 1985)
There is now fairly convincing evidence that since 1974-75 (which coincided with the launching of the Fifth Five Year Plan), the Indian economy has moved to a higher growth path. The successful implementation of the Sixth Five Year Plan has been a major contributory factor to this welcome shift in the growth curve. On the whole, the Sixth Plan has been fairly successful in sustaining and further strengthening the impulses for growth, modernisation and social justice.
Government of India Planning Commission